"Humanhood" in the Gospel of John - Thomaskutty, Johnson (HTS teologiese studies, 2021)
This article is an attempt to explore the theme of ‘humanhood’ in the Fourth Gospel. The most important questions to be posed at the outset are the following: who is the model human presented in the gospel as per the Johannine community standards? How can a person acquire humanhood status according to the Johannine community? The divine and human interaction in the life and ministry of Jesus dynamically introduces the life ethics and mission aspects of the Johannine community. According to the Johannine community standards, people can achieve ‘humanhood’ status exclusively in relation to Jesus. As the community of John emphasises humanhood in relation to Jesus, a person can overcome all sorts of human-made boundaries, including the sexual, racial and class-oriented boundaries through the mediation of Jesus. This further means that the all-inclusive mission of Jesus foregrounds a new criterion for ‘humanhood’ in the Johannine community context. The article concludes by stating that the Johannine understanding of humanhood can be considered as a paradigm in the contemporary global scenario.Contribution: This article contributes to the reader a wider hermeneutical framework and a new way forward in interpreting the gospel according to John by taking into consideration the humanhood aspects. As a theological and contextual interpretation of the Fourth Gospel, the article fits well within the scope of HTS Teologiese Studies/Theological Studies.